Analisis Penggunaan STID Pada Pelabuhan Auto Gate System - Yudanto, Leonardus Panggih (Peneliti.net, 2024)
Trucking activities at ports are activities that are closely related to loading and unloading activities. This trucking activity functions as a link between sea transportation activities and land transportation. To support the smooth running of trucking activities at the port, digitalization of the system at the port is needed. One example of digitalization at ports is the use of STID cards. The use of STID cards is a new breakthrough in supporting the era of digitalization at ports. This research focuses on analyzing the use of STID in ports. The method used is qualitative with data collection using a literature review. Based on the results of a literacy study, the use of STID at ports aims to streamline loading and unloading times at the dock and ensure security and safety of activities.